Uses and limitation of different thermometers for measuring heating efficiency of magnetic fluids. (5th May 2016) - Skumiel, A.; Hornowski, T.; Józefczak, A.; Koralewski, M.; Leszczyński, B.
Highlights: The system for determination of magnetic heat losses using four methods of temperature measurements was proposed. Thermometers used were: pyrometer, thermocouple, fiber optic and ultrasonic sensor. SAR coefficients describing heating processes were calculated. Uses and limitation of different thermometers were analyzed and discussed. The choice of proper thermometer and procedure is crucial in magnetic hyperthermia. Abstract: This paper presents the results of the heating of magnetic fluid (MF) containing magnetite nanoparticles. Volume concentration of magnetite nanoparticles ( ϕ V  = 2.76%) was determined from magnetic experiments. Mean diameter 〈 d 〉 = 12.7 nm and its standard deviation s  = 5.0 nm of the core of magnetic particles were obtained using TEM technique. Magnetic fluid heating experiments were carried out at a frequency of 440 kHz for magnetic field strength up to 3 kA⋅m −1 using lab-made experimental set-up. For temperature measurements, various kinds of devices were used: pyrometer, thermocouple thermometer, optical fiber temperature sensor and thermometer with ultrasonic sensor. Specific absorption rate (SAR) and temperature measurement error were calculated and discussed for all the thermometers used. The influence of eddy currents induced in a thermocouple on the determination of temperature of MF was described. The usefulness of different types of temperature measuring devices and their accuracy in determining the heating rate and the SAR coefficient of the magnetic fluid were analyzed and discussed.